Início de ativação muscular de estabilizadores primários e a capacidade física para avaliar estabilização lombo-pélvica - Geres, Gabriela Sanches; Negrão Filho, Rubem de Faria [UNESP]; Azevedo, Fábio Mícolis de [UNESP]; Jassi, Fabricio José; Fioravante, Isabela Soares Kishi; Alves, Neri [UNESP] (My University, 2010)
Introduction: Due to the high incidence of low back pain without apparent cause, different approaches to evaluate the lumbar instability has been proposed, such as surface electromyography to determine pre-activation and the ability of lumbar stabilization through functional physical assessment. In this context, the objective of this study was to evaluate the early activation of the primary stabilizing muscles in subjects without low back pain, with different physical abilities function (CFF). Method: Study participants were 20 subjects with 19.8 ± 1.4 years, 55.7 ± 8.8 kilos, 1.66 ± 0.08 m, of both sexes. The subjects underwent six Tests Physical Function (TFF) and the Test of Fast Moving Flexion Arm (TMRFB) to capture the electromyographic activity of the lumbar multifidus muscles (LM) and internal oblique - lower fibers (HI). Were assigned weights for each functional test and the result of the physical capacity of the final functional subject ranged from 0 to 100%. In the analysis of TMRB was considered the onset time of activation between the ML and HI. Results: Regarding TFF 2 (10%) subjects were considered to have normal physical capacity, 6 (30%) with good physical ability and 12 (60%) with regular physical capacity or poor. As for TMRFB average values of initiation of muscle activation in 75% of subjects were within the limits to characterize the condition of pre-muscle activation. Conclusion:The results obtained in the TFF were low compared with the CFF of asymptomatic subjects evaluated. This fact does not mean that the condition of stabilization of the subject is appropriate. However, the results obtained in the electromyographic examination to suggest that 25% of asymptomatic subjects tested did not have a proper condition of lumbar stabilization.

Devido à alta incidência de dor lombar sem causa definida, diversas abordagens para avaliar a instabilidade lombar têm sido propostas, tais como a eletromiografia de superfície para determinar pré-ativação e a capacidade de estabilização lombar por meio avaliação física funcional. Neste contexto, o objetivo do presente estudo foi avaliar o início de ativação dos músculos estabilizadores primários, em sujeitos sem dor lombar, com diferentes capacidades físicas funcionais (CFF). Método: Participaram do estudo 20 sujeitos com 19.8 ±1.4 anos, 55.7 ±8.8 quilogramas, 1.66 ±0.08 metros, de ambos os sexos. Os sujeitos foram submetidos a seis Testes Físicos Funcionais (TFF) e ao Teste de Movimento Rápido de Flexão do Braço (TMRFB) para captação da atividade eletromiográfica dos músculos multífido lombar (ML) e oblíquo interno – fibras inferiores (OI). Foram atribuídos pesos para cada teste funcional e o resultado da capacidade física funcional final dos sujeitos variou de 0 a 100%. Na análise do TMRB foi considerado o tempo de início de ativação entre o ML e OI. Resultados: Com relação ao TFF 2 (10%) sujeitos foram considerados com capacidade física normal, 6 (30%) com capacidade física boa e 12 (60%) com capacidade física regular ou pobre. Quanto ao TMRFB os valores médios de início de ativação muscular em 75% dos sujeitos encontraram-se dentro dos limites para caracterização da condição de pré-ativação muscular. Conclusão: Os resultados obtidos nos TFF mostram baixa relação com a CFF dos sujeitos assintomáticos avaliados. Tal fato não permite concluir que a condição de estabilização dos sujeitos seja adequada. Porém, os resultados obtidos na avaliação eletromiográfica permitem sugerir que 25% dos sujeitos assintomáticos testados não apresentam uma condição de estabilização lombar adequada.
Muscle activation of primary stabilizers and physical capacity to assess lumbar-pelvic stabilization
Keywords: Electromiography; Lumbar-pelvic stabilization; Functional physical evaluation; Eletromiografia; Estabilização lombo-pélvica; Avaliação física funcional